2022
DOI: 10.1021/acsnano.2c06359
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Atomic Chains for Ultimate-Scaled Electronics

Abstract: The continuous downscaling of semiconducting channels in transistors has driven the development of modern electronics. However, with the component transistors becoming smaller and denser on a single chip, the continued downscaling progress has touched the physical limits. In this Perspective, we suggest that the emerging one-dimensional (1D) material system involving inorganic atomic chains (ACs) that are packed by van der Waals (vdW) interactions may tackle this issue. Stemming from their 1D crystal structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 88 publications
0
24
0
Order By: Relevance
“…Furthermore, we observe various structural variations that correlate with the nanotube diameter, which agrees with prior research. ,,,, For ultranarrow nanotubes with an inner diameter less than 0.9 nm, we observe the presence of 1D single atomic chains, as reported in several previous studies. ,, , The stacking structure of multiple type-1 or type-2 chains can be stabilized within larger diameter nanotubes, as shown in Supporting Figures S11 and S12. Inside relatively wide nanotubes (typically larger than 1.2 nm), amorphous-type structures are found, as shown in Supporting Figure S13.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we observe various structural variations that correlate with the nanotube diameter, which agrees with prior research. ,,,, For ultranarrow nanotubes with an inner diameter less than 0.9 nm, we observe the presence of 1D single atomic chains, as reported in several previous studies. ,, , The stacking structure of multiple type-1 or type-2 chains can be stabilized within larger diameter nanotubes, as shown in Supporting Figures S11 and S12. Inside relatively wide nanotubes (typically larger than 1.2 nm), amorphous-type structures are found, as shown in Supporting Figure S13.…”
Section: Resultsmentioning
confidence: 99%
“…For example, previous studies have indicated that silica can be stabilized in the two-dimensional (2D) limit. , Similarly, one-dimensional (1D) confinement inside carbon nanotubes (CNTs) or boron nitride nanotubes (BNNTs) may be utilized to pack tetrahedral building blocks and realize crystalline phases with modified connectivity. Previous studies have indeed demonstrated the synthesis and stabilization of various materials inside nanotubes, including carbon nanomaterials, pnictogens (P, As, and Sb), halides, and transition-metal chalcogenides. Although these studies have shown interesting quasi-1D nanostructures and physical properties, ,,,, packing of tetrahedral building blocks has yet to be reported. Transition-metal chalcogenides with octahedral building blocks have been encapsulated in nanotubes, , but the tuning of the octahedral connectivity is limited due to the isotropic bonding nature.…”
Section: Introductionmentioning
confidence: 99%
“…21–23 Particularly, the unique adjustable wide bandgap of MOSs endows them with ideal properties to construct short-wavelength photoconductors, especially considering the large surface-to-volume ratio of one-dimensional (1D) nanostructures. 24–26 To be specific, we have previously developed a fabrication process combining low-temperature combustion and electrospinning techniques to make indium zinc oxide (InZnO) nanowires for high-performance ultraviolet (UV) photodetectors. 27 We also tuned the corresponding electrical response by configuring multi-cation MOSs.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional semiconductors, photodetectors ground on 1D vdW materials demonstrate advantages in the following aspects: (I) The dangling bonds-free surface of 1D vdW materials is insensitive to adsorbates, surface contaminations, and lattice defects, which is beneficial for fabricating photodetectors with ultrahigh speed and highly sensitive photoresponse. (II) Giant anisotropy induced by the distinctly different bonding between intrachain (covalent bonding) and interchain (vdW interaction) in 1D vdW nanowires is a prerequisite for polarized photodetection. , (III) The intrinsic 1D crystal structure is conducive to fabricating flexible and integrated photodetectors. , (IV) 1D vdW nanowires with chirality provide a platform for the exploration of multiple mechanisms coupling and Stokes photodetectors. (V) Weak vdW interaction in the interchain of 1D vdW materials is essential for fabricating hybrid photodetectors. (VI) Spin–orbit qubit emerges in 1D nanowires due to their strong spin–orbit coupling, which can be used to respond to an external AC electric field, namely, the effect of spin resonance of electric dipole, playing a crucial role in developing photodetectors based on different physical mechanisms. …”
mentioning
confidence: 99%
“…(II) Giant anisotropy induced by the distinctly different bonding between intrachain (covalent bonding) and interchain (vdW interaction) in 1D vdW nanowires is a prerequisite for polarized photodetection. 13,14 (III) The intrinsic 1D crystal structure is conducive to fabricating flexible and integrated photodetectors. 8,15 (IV) 1D vdW nanowires with chirality provide a platform for the exploration of multiple mechanisms coupling and Stokes photodetectors.…”
mentioning
confidence: 99%